Hello all.
Is the following expression true?
[$\displaystyle ( p \equiv q ) \wedge ( r \equiv s ) $] $\displaystyle \Rightarrow$ [($\displaystyle p \wedge r ) \equiv ( q \wedge s )$]
If yes, please prove it.
Hello all.
Is the following expression true?
[$\displaystyle ( p \equiv q ) \wedge ( r \equiv s ) $] $\displaystyle \Rightarrow$ [($\displaystyle p \wedge r ) \equiv ( q \wedge s )$]
If yes, please prove it.
Thanks
Yes - see the attached truth table for the proof.
The columns are evaluated in order from (1) to (7) - column (7) being the final result, which shows TRUE on every line.